International Competitiveness and Market Access of Indian Floriculture products: an Extension perspective - K. Venkateswaran; G Rajendran (Journal of Agricultural Extension Management, 2025)
This article attempts to elucidate the contemporary changes in the floriculture sector in the last two decades, especially, after the liberalisation, globalization and implementation of trade reforms which has brought structural changes in the floriculture sector. Most of the floriculture products are produced for export. The first aim of the article is to estimate the effects of the trade reform measures in terms of trade elasticity of regulations and competitiveness of Indian floriculture exports. In spite of the generalized acknowledgement of the growing liberalisation of trade between countries, there are still numerous obstacles to trade, more of the nontariff type. It also aims to contribute to the literature on quantifying the economic impact of Indian trade reforms related to the floriculture industry. The constant market share (CMS) model has been used to obtain insight into the overall dynamics of the export markets, trade flows and competitiveness of Indian floriculture exports. Based on the results, a suitable international market oriented extension approach can be suggested for the floriculture sector.